Clinical Trial: CYP2D6 Related Dose Escalation of Tamoxifen in Breast Cancer Patients With Iranian Ethnic Background Resulted in Increased Concentrations of Tamoxifen and Its Metabolites - Khalaj, Zahra; Baratieh, Zohreh; Nikpour, Parvaneh; Schwab, Matthias; Schaeffeler, Elke; Mokarian, Fariborz; Khanahmad, Hossein; Salehi, Rasoul; Mürdter, Thomas E.; Salehi, Mansoor (Frontiers in Pharmacology, 2019)
Introduction: The polymorphic enzyme cytochrome P450 2D6 (CYP2D6) catalyzes a major step in the bioactivation of tamoxifen. Genotyping of clinically relevant CYP2D6 alleles and subsequent dose adjustment is a promising approach to individualize breast cancer therapy. The aim of this study was to investigate the relationship between the plasma levels of tamoxifen and its metabolites and different CYP2D6 genotypes under standard (20 mg/d) and dose-adjusted therapy (Registration ID in Iranian Registry of Clinical Trials: IRCT2015082323734N1). Material and methods: Using TaqMan® assays common alleles of CYP2D6 (*1, *2, *4, *5, *6, *10, *17 and *41) and gene duplication were identified in 134 breast cancer patients. Based on CYP2D6 genotypes patients with an activity score 1 (n=15) and 0 to 0.5 (n=2) were treated with tamoxifen adjusted dosage of 30 and 40 mg/d, respectively. The concentration of tamoxifen and its metabolites before and after 4 and 8 months of dose adjustment were measured using LC-MS/MS technology. Results: At baseline, (Z)-endoxifen plasma concentrations (33 ± 15.5, 28.1 ± 14, 26.6 ± 23.4, 14.3 ± 8.6 and 10.7 ± 5.5 for EM/EM, EM/IM, EM/PM, IM/IM and PM/PM, respectively) and the metabolic ratio (Z)-Endoxifen / N-desmethyltamoxifen (0.0558 ± 0.02, 0.0396 ± 0.0111, 0.0332 ± 0.0222, 0.0149 ± 0.0026 and 0.0169 ± 0.0177 for EM/EM, EM/IM, EM/PM, IM/IM and PM/PM, respectively) correlated with CYP2D6 genotype (Kruskal-Wallis p=0.013 and p<0.0001, respectively). Dose escalation to 30 and 40 mg/d in patients with a CYP2D6 activity score of 1 (n=15) and 0-0.5 (n=2) resulted in a significant increase in (Z)-endoxifen plasma levels (22.17 ± 24.42, 34.43 ± 26.54 and 35.77 ± 28.89 at baseline, after 4 and 8 month, respectively, Friedman p= 0.0388) along with the plasma concentrations of tamoxifen and its other metabolites. No severe side effects were recorded during dose escalation. Conclusions: For the first time, we show the feasibility of dose escalation of tamoxifen in breast cancer patients with compromised CYP2D6 activity and Iranian ethnic background to increase the plasma concentrations of (Z)-endoxifen.